Development of Global Consensus of Dengue Virus Envelope Glycoprotein for Epitopes Based Vaccine Design - Hussain, Mazhar; Idrees, Muhammad; Afzal, Samia (Current Computer - Aided Drug Design, 2015)
Dengue virus (DENV) is the member of Flaviviridae and causative agent of Dengue Haemorrhagic Fever and Dengue Shock Syndrome. Every year, around 70% of the world population is at risk, due to epidemic episodes orchestrated by one or more of its serotypes. So, a tetravalent DENV vaccine is needed which may induce the immune response against all four DENV serotypes. In this study, B-cell and T-cell epitopes have been predicted from the DENV envelope glycoprotein (Eg) using a consensus based approach in complement with the physico-chemical property (PCP) conservancy analysis. Through DENV-Eg analysis, a total of 7 PCP conserved, water soluble, in vitro and in vivo stable epitopes were predicted which may induce the B-cell and T-cell mediated anti-viral immune response.
Keywords: in silico design